Modeling Fair Wage Implementation within a Mixed Economy Framework: Insights from Islamic Economic Principles - Sanusi Gazali Pane; Sugianto (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
Fair wage determination involves subjective perceptions influenced by individual values and contextual understanding. This study explores fair wage concepts within Islamic banking through a cross-sectional survey examining respondents across various positions and industrial relations statuses. The research incorporates transparency and information openness as key variables, analyzing fair wages beyond nominal amounts to encompass processes shaping individual perceptions. An Islamic economic perspective guides the analysis of determinant factors. The study employed a survey of Islamic banking professionals to assess perceptions of wage fairness and their relationships with job satisfaction and family welfare. Findings reveal that 92.36% of respondents perceive their wages as fair, with the highest level of satisfaction (96.1%) attributed to wage comparability across similar roles. The lowest satisfaction (76.6%) was observed for religious culture aspects. This research contributes to Islamic economic theory by demonstrating the contemporary relevance of Islamic teachings on economic justice in modern industrial contexts, highlighting social benefits as crucial determinants in fair wage concepts for policy development.